The End of Directing – A Foundation Study for Contemporary European Theatre Making. Iulia Popovici (ed.), “The End of Directing, The Beginning of Theatre-Making and Devising in European Theatre”, 2015, 327 p., ISBN : 978-606-8437-56-9, Sibiu International Theatre Festival Book Collection. - WOHL, Eugen (Studia Universitatis Babeș-Bolyai Dramatica, 2023)
The Sibiu International Theatre Festival has developed a section of conferences, theoretic debates and book printing. Usually the festival brings to light contemporary theatre plays but also theoretical volumes, that deal with contemporary issues regarding theatre. This year, they propose a very important and expected collection of studies and interviews: The End of Directing, The Beginning of Theatre Making and Devising in European Theatre. The volume in question comes as a meaningful study for a market that has really few contemporary theoretical contributions regarding national or international independent production. Usually, specialists and students learn from papers or blogs what European theatre is up to. Offering a critical approach on a phenomenon that is growing every day, that of collective work in theatre, the volume is structured in two sections: studies about independent performances in specific countries and interviews with representative theatre makers.